International Relations Are What Humans Communication Literally Creates - Nabil Hamidi (My University)
What if human phenomena are nothing other than human communications? If political, legal, and social systems are subject to government regulations and restrictions, how is it possible that they nevertheless behave in socially constructed yet internally coherent ways? This paper advances a foundational claim: human systems exist only insofar as the human brain possesses the neuropsychological capacity to communicate. Societies do not precede communication, nor do they abstractly generate it; rather, societies are continuous products of physical communicative processes occurring in human brains. Communication does not explain why human phenomena exist in the first place, but it organizes and explains everything that is human and political. It is the fundamental and first neurobiological principle that explains why, when, where, how, who, and what humans politically and humanly do and feel in the world system as both bodies and brains.